Emergency laparoscopic resection of spontaneous rupture of hepatocellular carcinoma: a case report - Allim Khairuddin; Guang, Hong Ong; Jun, Sam Tan; Syamim Johan; Vee, Chuan Hoe; Mohd Sharifudin Sharif; Firdaus Hayati (Elsevier Ltd, 2019)
Introduction Laparoscopic liver resection is currently performed as a therapeutic modality in hepatocellular carcinoma (HCC). In an emergency setting such as bleeding or rupture, however it has not been well documented.